Methods in yeast genetics : a Cold Spring Harbor Laboratory course manual - Burke, Dan; Dawson, Dean; Stearns, Tim (Cold Spring Harbor Laboratory Press, 2000)
Yeast is an ideal eukaryotic microorganism for biochemical and genetic studies, particularly since its complete genome sequence became available. The Cold Spring Harbor Laboratory Yeast Genetics Course has kept pace with the field over the last 30 years, combining essential standard methods with the latest technologies, and its course manual has followed suit. In the new 2000 edition, most of the experiments have been revised and several new experiments and techniques have been added, including the 2-hybrid system, PCR-based methods, and isolation of chromatin. This manual remains a primary source for newcomers to the field as well as the established investigator, providing complete, detailed protocols and techniques of proven robustness.
Keywords: genetika, lékařská genetika; Yeasts; kvasinky; biologie